Sensory trail as pedagogical action in early childhood education - Pereira , Simone Maria Stertz; Siqueira , André Boccasius (Seven Editora, 2023)
The present work began with a research project at the Municipal School of Early Childhood Education Meu Cantinho in the municipality of Rolante, Rio Grande do Sul. It is perceived that, over the years, the relationship between human beings and nature has been distancing itself. The theme of this research is related to the Environment and the learning of children of Early Childhood Education - Garden A, through a pedagogical dynamic called sensory track. It aimed to "provide students with the experience of perceiving elements of nature through the senses". With this pedagogical proposal, the students' senses were stimulated, generating a relationship of connection with nature, as well as it was possible to develop some skills, among them motricity, emotional, cognitive, observation and experience with the natural environment. It is observed that it is possible to unpair early childhood education with methodologies interconnected with nature. DOI:https://doi.org/10.56238/ptoketheeducati-030